21st Century Change Drivers: Considerations for Constructing Transformative Models of Special Education Teacher Development. (May 2016) - Rock, Marcia L.; Spooner, Fred; Nagro, Sarah; Vasquez, Eleazar; Dunn, Cari; Leko, Melinda; Luckner, John; Bausch, Margaret; Donehower, Claire; Jones, Jennie L.
Contemporary challenges confronting special education teachers include, in part, workload, role ambiguity, evaluation, and shortages. Based on these and other challenges, the piece-meal fragmented approach to pre- and in-service training, which exists currently, needs to be replaced with 21st century models of special education teacher development that are seamless, technology enabled, comprehensive, cohesive, and career spanning. In this article, the authors briefly address persistent and unresolved challenges, identify contemporary change drivers, and discuss ways in which teacher education professionals could leverage the drivers to inform the development of 21st century models for special education teacher development aimed at improving outcomes for students with disabilities. Change drivers include the digital revolution, the diversity gap, the credibility factor, the demand for collective impact, and the culture of we. The authors conclude with a call to action.